ANALISIS FUNDAMENTAL DALAM PENGAMBILAN KEPUTUSAN INVESTASI SAHAM PERUSAHAAN PERKEBUNAN PERIODE 2008-2015 - Pratiwi, Irma Dwi; Nugraha, Nugraha (Business Education Program of Universitas Pendidikan Indonesia, 2017)
Objective – For fundamental analysis and to know the description of Earning Per Share and Price Earning Ratio as a basis for consideration in decision making of stock investment in plantations sub-sector period 2008-2015.Design/methodology/approach – This type of research is descriptive method with a total sample of 7 metal and allied sub-sector companies listed on the Indonesian Stock Exchange. The analysis technique used is fundamental analysis with EPS and PER approaches. The design of this research is the method of time series design with a period of research for 8 years.Findings – Based on the results of fundamental analysis with EPS and PER approach can effectively assist investors in assesing the company’s stock on making decision of stock investment in plantations sub sector.Originality/value – The difference in this study lies in the object of research, study time, measuring tools, literature used, the theory used and the results of research. Keywords: Fundamental analysis, Investment Decision Making, Stocks, Earning Per Share (EPS), Price Earning Ratio (PER), Intrinsic ValueArticle Type: Case Study